Nitti e gli interventi speciali per il Mezzogiorno del 1904. Per una comparazione tra il caso napoletano e quello lucano - Donato Verrastro (Democrazia e Diritti Sociali, 2021)
The article proposes a comparative reading of the two extraordinary interventions on and for the Mezzogiorno promoted by Zanardelli and Giolitti, namely one for Basilicata (l. 140/1904) and the other for Naples (l. 351/1904). The ‘special workshops’ that would follow identified in Francesco Saverio Nitti one of the main protagonists: de facto extender of the industrialist project for Naples, he was very critical of the traditional scheme launched for Basilicata, which he felt lacked the ambitiously industrialist breath that could have prevented the Province from being nailed once again to its primitive agrarian structures. In particular, starting from a reading of the historical context, the essay highlights common aspects and differences between the regulatory arrangements, touching on the issues that would be at the center of the political debate of the liberal era, such as the importance of technical studies and preliminary investigations, institutional aspects, the contrast between the industrial model linked to the «conquest of hydroelectric power» and the one connected to a more traditional matrix, based on agriculture and infrastructure. Overall, however, the essay tries to describe how, at the beginning of the twentieth century, a pioneering response to the so-called ‘Southern Question’ implied, beyond the unpredictable outcomes, also the attempt to break ancient immobilities, as well as an extraordinary commitment that best interpreted the spirit and meaning of the times.